Assessing patient satisfaction with implant prosthetic work. A preliminary questionnaire-based study - Arin Sava; Ondine Lucaciu; Simion Bran; Florin Onişor; Sorina Sava; Alexandru Meşter; Ovidiu Aghiorghiesei; Roxana Bălan; Radu Septimiu Câmpian (Amaltea Medical Publishing House, 2019)
Objective. To evaluate the quality of life of edentulous patients with implant prosthetic work. Methods. Retrospective study, between 2015 and 2016, with a group of 50 patients in the over-implantation phase. Patients responded to a satisfaction questionnaire following overdenture prosthesis. Results. Overdenture has improved the quality of life of patients by regaining their self-esteem, regaining the aesthetic, phonetic and mastication functions, as well as the possibility of using a solid consistency diet without the occurrence of pain. Conclusion. The use of overdenture prosthesis is a treatment that gives patients satisfaction from all points of view (functional, psychological, aesthetic and economic). To reflect the reality, future studies will need to obtain information from a larger number of subjects from different backgrounds, being treated in different clinics.